Revisão da efetividade da análise de vibrações para diagnóstico preditivo de falhas de equipamento em Indústria Química - Gross, Matheus (Universidade Federal de São Carlos, 2022)
In the 4.0 industry, it's common the presence of technological solutions to predict equipment failures. The vibration analysis is used in the predictive maintenance area, and can can be applied to diagnose failures in the beginning with the vibration of equipment in operation. The present study was made in a chemical industry from the countryside of São Paulo State. It has a monthly collect of vibration from a dedicated technician. Seven equipment groups were selected (motoreductors, pumps and motovariators) considered to be critical for the process. For this study, the evolution of vibration RMS values were evaluated. Comparisons were performed between the maintenance made in the selected equipment, with the partial and total failures, and the diagnosis done by the graphs analysis. The possibility of anticipating failuares ahead of time was observed when the vibration analysis was collected in the right period of time. It was also observed that the lack of measurement routes harnessed the premature diagnosis of failures and unplanned events for the productive areas.
Review of the effectiveness of vibration analysis for predictive diagnosis of equipment failures in the Chemical Industry
Keywords: Análise de vibrações; Manutenção preditiva; Diagnóstico de falha; Vibration analysis; Predictive maintenance; Failure diagnosis; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO